Factors Associated with Potential Food-Drug Interaction in Hospitalized Patients: A Cross-Sectional Study in Northeast Iran - Mostafa Abdollahi; Saeid Eslami; Zhila Taherzadeh; Shayesteh Salehi; Marzieh Ebrahimi (Mashhad University of Medical Sciences, 2018)
Background: The minimization of adverse food-drug interactions will improve patient care by optimizing the therapeutic effects and maintaining proper nutritional status. Aim: The aim of the present study was to find the main factors that may place the hospitalized patients at risk of potential food-drug interactions. Method: This cross-sectional, descriptive study was conducted on 400 inpatients admitted to the Department of Internal Medicine of a teaching hospital in Mashhad, Northeast Iran, within 20 March 2013 to 20 April 2013. The potential food-drug interactions were evaluated for 19 commonly prescribed medications. The main factors (e.g., age, gender, education level, number of medications, and duration of the disease) that may place the patients at risk of potential food-drug interactions were analyzed for each patient. Results: Out of the 19 commonly prescribed medications, 17 drugs (89%) were not properly used with respect to meal. Furthermore, 14 commonly prescribed drugs were found to have a high frequency (≥50%) of potential food-drug interactions. Most of the patients (n=359, 89.8%) consumed their medicines at inappropriate time with respect to meals. The results of a multiple logistic regression after adjustment for confounders revealed that the age [β=0.005, CI: 0.0-0.01; P=033], number of medications [β=0.1, CI: 0.083-0.117; P